2021
DOI: 10.1016/j.sjbs.2021.05.058
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic acid activates the Nrf2 signaling pathway to alleviate impairment of spleen cellular immunity in intrauterine growth restricted rat pups

Abstract: Intrauterine growth retardation (IUGR) impairs immune function in children. IUGR is associated with an imbalance of oxidative stress and abnormal apoptosis. Therefore, an IUGR rats model was established to determine the antioxidant capacity and apoptosis in newborn IUGR rats and explored whether these effects were regulated after Docosahexaenoic acid (DHA) supplementation to rat pups. First, eight normal-birth-weight (NBW) and eight IUGR neonatal rats (a 10% low-protein diet) were used to obtain the antioxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Lutein supplementation has shown dose-dependent enhancements in adult mice's immune functions, such as increased natural killer cell activity and lymphoproliferative response in the spleen [79]. While the specific functions of lutein in the neonatal spleen remain unclear, it may aid spleen development and immunomodulation [80,81]. In this study, the lutein emulsion group displayed higher spleen lutein concentration, potentially benefiting spleen development and neonatal rat immunity.…”
Section: Cta-stabilized Lutein Emulsion Improved Tissue Lutein Statusmentioning
confidence: 70%
“…Lutein supplementation has shown dose-dependent enhancements in adult mice's immune functions, such as increased natural killer cell activity and lymphoproliferative response in the spleen [79]. While the specific functions of lutein in the neonatal spleen remain unclear, it may aid spleen development and immunomodulation [80,81]. In this study, the lutein emulsion group displayed higher spleen lutein concentration, potentially benefiting spleen development and neonatal rat immunity.…”
Section: Cta-stabilized Lutein Emulsion Improved Tissue Lutein Statusmentioning
confidence: 70%
“…The number of studies conducted on animal models is limited to 15 cases. Twelve of them involved rats [ 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ], whereas three were conducted in mice [ 43 , 67 , 68 ]. Seven studies were focused on the liver [ 43 , 55 , 56 , 59 , 60 , 61 , 68 ], six on the nervous system [ 58 , 59 , 61 , 62 , 63 , 64 ], three on plasma/serum [ 55 , 65 , 68 ], and only one study was reported for the kidney [ 56 ], retina [ 57 ], spleen [ 66 ], stomach [ 67 ], and erythrocytes [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Twelve of them involved rats [ 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ], whereas three were conducted in mice [ 43 , 67 , 68 ]. Seven studies were focused on the liver [ 43 , 55 , 56 , 59 , 60 , 61 , 68 ], six on the nervous system [ 58 , 59 , 61 , 62 , 63 , 64 ], three on plasma/serum [ 55 , 65 , 68 ], and only one study was reported for the kidney [ 56 ], retina [ 57 ], spleen [ 66 ], stomach [ 67 ], and erythrocytes [ 65 ]. In addition, four studies were carried out in normal conditions [ 55 , 56 , 61 , 65 ], four studies in association with injuries [ 43 , 59 , 63 , 64 ], and seven studies in both conditions [ 57 , 58 , 60 , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations